"Tiempo y temperatura para la torrefacción de la semilla de fruta de pan (Artocarpus Alttilis) con chocolate de cobertura" - Zamora Vazco, Geomara Karina (2018)
The objetive of the reserach investigation was to evalute the time and temprature for roasting the breadfruit see (Artocarpus altilis) with cover chocolate. A completely randon desing was applied within a 2x2 factorial arrangement, within....................................................................................................................